The Influence of Local Potential-Based Comic Media on Environmental Literacy and Students' Conceptual Understanding - Desy Destania; Ismail Efendi (PAIDAGOGIA: Jurnal Inovasi Pendidikan dan Pembelajaran, 2024)
This research aims to determine (1) the influence of local potential-based comic media on environmental literacy and students' conceptual understanding in high schools in West Sumbawa Regency and (2) the differences in environmental literacy and conceptual understanding of students in the two experimental classes. The research follows a Pre-Experimental design with a one-group pre-test and post-test design. The population includes all high school students in West Sumbawa Regency, with a sample of 38 students from Class XI at SMA 1 Taliwang and SMA 2 Taliwang. Research instruments include questionnaires and tests, where the questionnaire measures students' environmental literacy, and the test evaluates students' conceptual understanding. Data analysis employs N-Gain and t-test. N-Gain is utilized to assess the impact of local potential-based comic media on environmental literacy and conceptual understanding, while the t-test is applied to identify differences in environmental literacy and conceptual understanding between the experimental classes. The research findings indicate that implementing local potential-based comic media significantly influences environmental literacy and conceptual understanding in both experimental classes, with an N-Gain value of 0.5 in the moderate category. Further analysis reveals no significant differences in conceptual understanding and environmental literacy between the two experimental schools (Sig > 0.05).